Atomic layer deposition supercycle approach applied to the Al-doping of nearly saturated ZnO surfaces. Issue 5 (1st March 2021) - Ramírez-Esquivel, Obed Yamín; Mazón-Montijo, Dalia Alejandra; Cabrera-German, Dagoberto; Martínez-Guerra, Eduardo; Montiel-González, Zeuz
Abstract: Current research on transparent conductive oxides deals with the development of environmentally friendly materials having competitive electrical and optical properties. Also, the synthesis methods need to be compatible with the state-of-the-art microelectronics and miniaturization. ZnO films doped with Al (AZO) via Atomic Layer Deposition (ALD) have been subjected to thorough investigation for the latter. However, the conventional doping schemes in ALD seem to have reached their limit and alternative approaches are currently being explored. This work contributes to the improvement of the Al-doping efficiency of ZnO by the ALD supercycle approach, applying the doping-cycle on nearly saturated ZnO surfaces. The electrical ( ρ  = 1.3 × 10 −3 Ωcm, n  = 3.79 × 10 20 cm −3, and μ  = 12.3 cm 2 /Vs) and optical (%T > 75) properties demonstrated typical values obtained by others applying the supercycle methodology. However, the main finding of this work is the trend observed in the electrical and optical properties, which suggests that the Al solubility limit was not reached as a result of the interaction between the dopant agent and the nearly saturated ZnO surfaces. This is also evidence that the dopant atoms do not become inactive once the compensation effect between substitutional doping and structural defects, has been established. These results open the possibility of exploring the incorporation of more Al into the ZnO structure following and optimizing the doping scheme used here, which at the same time, promises materials that could substitute indium-tin-oxide in many optoelectronic applications, attending the well-known environmental and economic issues.